Comparing sediment preservation methods for genomic biomonitoring of coastal marine ecosystems. (December 2021) - Dully, Verena; Rech, Giulia; Wilding, Thomas A.; Lanzén, Anders; MacKichan, Kate; Berrill, Iain; Stoeck, Thorsten
Abstract: To avoid loss of genetic information in environmental DNA (eDNA) field samples, the preservation of nucleic acids during field sampling is a critical step. In the development of standard operating procedures (SOPs) for eDNA-based compliance monitoring, the effect of different routinely used sediment preservations on biological community structures serving as bioindicators has gone untested. We compared eDNA metabarcoding results of marine bacterial communities from sample aliquots that were treated with a nucleic acid preservation solution (treated samples) and aliquots that were frozen without further treatment (non-treated samples). Sediment samples were obtained from coastal locations subjected to different stressors (aquaculture, urbanization, industry). DNA extraction efficiency, bacterial community profiles, and measures of alpha- and beta-diversity were highly congruent between treated and non-treated samples. As both preservation methods provide the same relevant information to environmental managers and regulators, we recommend the inclusion of both methods into SOPs for biomonitoring in marine coastal environments. Highlights: We assessed effects of sample preservation for eDNA-based biomonitoring. We compared freezing versus preservation-solution treatment. DNA extraction efficiency was highly congruent among treatments. Bacterial community profiles as bioindicators were highly similar among treatments. Standard Operating Procedures (SOPs) for biomonitoring can use both treatments.